Teacher Strategies in Implementing Guidance Counseling To Improve Students' Morals - Haerunnisa, Wulan; Askar, Askar; Saguni, Fatimah (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2024)
This research aims to determine teachers' strategies in implementing guidance and counseling to instill morals in students. This research uses a qualitative method in which data collection is carried out through observation, in-depth interviews, and analysis of written documentation. Meanwhile, the data was analyzed using a thematic approach to find themes in the data collected in the field. The research results show that the teacher's strategy in implementing counseling guidance to instill student morals has been carried out well through several methods that the school has determined. Teacher strategies in implementing counseling guidance include oral form. The second strategy is counseling guidance in the form of practice. The results of this research also show that the supporting factors in cultivating students' morals at the Alkahiraat Senior Islamic High School are the family environment and infrastructure, and the inhibiting factors are the lack of support and attention from parents and the influence of peer environment. Suggestions for students at the Alkhairaat Alkahiraat Islamic Junior High School Palu are that they always be aware of their responsibilities as servants, obey the commands of Allah SWT, and stay away from his prohibitions. This will create students with noble morals, as we all hope for, according to the teachings of the Al-Qur'an and Hadith.